Uncertainty and strategic decision making - Sund, Kristian J., 1975-; Galavan, Robert J.; Huff, Anne Sigismund (New horizons in managerial and organizational cognition, 2016)
The study of management and organization has transitioned from approaches to deal with steady state management, to approaches that can cope with unknown or unknowable futures. The strategy field has has moved from business policy, through strategic planning, onto strategic management and now grapples with dynamic contexts as the new normal. In that trend the field has seen a broad movement in research interests in corporate and competitive strategies towards an emphasis on the managers strategic role. Through this shift, strategy has moved from a concept of something organizations have towards something that managers do. This has happened while traditional boundaries of industries have become permeable and even melted away. Managers tasked with doing strategy have lost not just the certainty of a goal-oriented future, but also the certainty of understanding their current position. Decision-making tools have now moved from answer generators to scenario builders. When decisions can rely less on evidence and certainty, it is managers that take up the slack and fill the void. This book focuses on the challenge of making strategic decisions in conditions of uncertainty.